Respuesta :
Answer:
Step-by-step explanation:
[tex]\sqrt{2z}[/tex] + 3 = -z
[tex]\sqrt{2z}[/tex] = -z - 3
Square both sides , we have
2z = [tex](-z-3)^{2}[/tex]
2z = [tex]z^{2}[/tex] + 6z + 9
re arranging the equation , we have
[tex]z^{2}[/tex] + 6z - 2z + 9 = 0
[tex]z^{2}[/tex] + 4z + 9 = 0
This will give a complex roots , solving by quadratic formula
z = -2 + [tex]\sqrt{5}[/tex]i , -2 - [tex]\sqrt{5}[/tex]i
Answer:
If you mean √2z + 3 = -z, the answer is ∅
If you mean √2 z + 3 = -z
√2 z + 3 = -z
√2 z = -z - 3
√2 z + z = - 3
z(√2 + 1) = -3
z = -3 / (√2 + 1)
z = -3 (√2 - 1)